2022
DOI: 10.1021/acs.jmedchem.2c00803
|View full text |Cite
|
Sign up to set email alerts
|

Development of Inhibitors Targeting the V-Domain Ig Suppressor of T Cell Activation Signal Pathway

Abstract: Blockade of cytotoxic T lymphocyte antigen 4 (CTLA-4) and programmed cell death-1/programmed cell death-ligand 1 (PD-1/PD-L1) has produced considerable therapeutic effect, but only in a fraction of patients, so more targets are being investigated. VISTA (V-domain Ig suppressor of T cell activation) is a novel immune checkpoint that is broadly expressed within hematopoietic cells and multiple cancers (low expressing frequency on solid tumors), particularly those with a poor immunotherapy response rate. As a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Tumor occurrence and development are largely driven by the activation of inhibitory immune checkpoint pathways, which impair the antitumor activities of T cells. Blocking the VISTA pathway can reactivate T cells and enhance their cytotoxicity against tumor cells . SKOV3 cells, which express high levels of VISTA protein, were cocultured with PBMCs.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor occurrence and development are largely driven by the activation of inhibitory immune checkpoint pathways, which impair the antitumor activities of T cells. Blocking the VISTA pathway can reactivate T cells and enhance their cytotoxicity against tumor cells . SKOV3 cells, which express high levels of VISTA protein, were cocultured with PBMCs.…”
Section: Resultsmentioning
confidence: 99%
“…Hong et al. fabricated tumor tissue slices from patients with clear cell renal cell carcinoma (ccRCC) to evaluate the antitumor effectiveness of a V‐domain Ig suppressor of T‐cell activation (VISTA) inhibitor, which is a candidate immune checkpoint inhibitor (ICI) 87 . The results indicated that all tested samples responded to the anti‐VISTA monoclonal antibody and produced TNF‐α, with 20% of ccRCC samples showing a synergistic effect when treated with a combination of VISTA and PD‐1 inhibitors.…”
Section: Application Of Civms In Drug Development and Precision Medicinementioning
confidence: 99%
“…Deficiency or blockade of VISTA enhances antitumor immunity in multiple tumor types, such as melanoma, pancreatic, prostate, and colon carcinoma. VISTA is also an important target for autoimmune diseases and its activation could be effective for the treatment of autoimmune diseases such as lupus. Currently, only few small-molecule antagonists or agonists of VISTA have been identified. Clinical trials are in progress of four VISTA-targeting compounds, including three anti-VISTA mAbs (CI-8993, W0180, and HMBD-002) and CA-170. However, recent studies reported that CA-170, the first clinical small-molecule inhibitor of PD-L1 and VISTA, exhibits weak binding affinity to PD-L1 and VISTA. , …”
Section: Introductionmentioning
confidence: 99%